Review on substituted 1, 3, 4 thiadiazole compounds - Manimaran T; Anand Raj M; Jishala MI; Gopalasatheeskumar K (International Journal of Pharmacy and Analytical Research, 2022)
The review was carried out to discuss in detail about the substituted 1,3, 4 thiadiazole compounds. heterocyclic compounds such as thiazoles, thiadiazoles, indoles, oxadiazoles, benzisoxazoles and pyrroles have been successfully used as Antibacterial, Anticancer, Antipyretic, Schistosomicidal, Hypoglycemic, Antihypertensive, Anti-tubercular, Anti-inflammatory and Anti-HIV agents. All large number of organo-sulfur compounds occur in living and non- living object. They belong to open chain, alicyclic, aromatic and heterocyclic types of compounds containing sulfur atoms or atoms as a part of chain/ring or both in the structure. In this review briefly study about the Struct ure and reactivity of 1,3,4-thiadiazoles, Characteristic reactions, Characteristic features of 1,3,4-thiadiazole, Methods of synthesis, biological interest. And in this review can be concluded that many researches had investigated on substituted thiodiazole compounds having the biological activities.